The Response to September 11: A Disaster Case Study - Michael A. Crane (Ubiquity Press, 2014)
Background: The response to 9/11 continues into its 14th year. The World Trade Center Health Program (WTCHP), a long-term monitoring and treatment program now funded by the Zadroga Act of 2010, includes >60,000 World Trade Center (WTC) disaster responders and community members (“survivors”). The aim of this review is to identify several elements that have had a critical impact on the evolution of the WTC response and, directly or indirectly, the health of the WTC-exposed population. It further explores post-disaster monitoring efforts, recent scientific findings from the WTCHP, and some implications of this experience for ongoing and future environmental disaster response. Findings: Transparency and responsiveness, site safety and worker training, assessment of acute and chronic exposure, and development of clinical expertise are interconnected elements determining efficacy of disaster response. Conclusion: Even in a relatively well-resourced environment, challenges regarding allocation of appropriate attention to vulnerable populations and integration of treatment response to significant medical and mental health comorbidities remain areas of ongoing programmatic development.